2014
DOI: 10.2355/isijinternational.54.212
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Behavior of Ti,Mo-added Low Carbon Steels with Interphase Precipitation

Abstract: Tensile behavior and structure-property relationship of ferritic steels with nano-sized carbide dispersion were invesigated using Ti-added steel and Ti,Mo-added low carbon steels. By austenitizing followed by isothermal heat treatment at 700°C, polygonal ferrites containing very fine carbides of TiC and (Ti,Mo)C were obtained in the Ti-added and the Ti,Mo-added steels, respectively. The size of such carbides was finer in the Ti,Mo-added steel than in the Ti-added steel at the same isothermal holding. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(80 citation statements)
references
References 31 publications
4
74
1
1
Order By: Relevance
“…Orowan looping mechanism also does not mean a strength reduction, as Gutierrez-Urrutia and Raabe [27] and Sun et al [39] showed a great Orowan strengthening but at a great expense of ductility. Kamikawa et al [29] published a work on strength improvement through the Orowan looping mechanism without the loss of ductility. Yet, such strength increment (200-300 MPa) is minute when compared to the strength enhancement (1 GPa) by the precipitate shearing mechanism.…”
Section: The Strengthening Mechanisms Of Nano-scale Precipitates Strementioning
confidence: 99%
See 4 more Smart Citations
“…Orowan looping mechanism also does not mean a strength reduction, as Gutierrez-Urrutia and Raabe [27] and Sun et al [39] showed a great Orowan strengthening but at a great expense of ductility. Kamikawa et al [29] published a work on strength improvement through the Orowan looping mechanism without the loss of ductility. Yet, such strength increment (200-300 MPa) is minute when compared to the strength enhancement (1 GPa) by the precipitate shearing mechanism.…”
Section: The Strengthening Mechanisms Of Nano-scale Precipitates Strementioning
confidence: 99%
“…Again, no reduction of the uniform elongation was observed, suggesting a small increment (0.6 nm in diameter) in the size of precipitates while maintaining a high number density (in the order of 10 24 m −3 ) through nano-scale-co-precipitation can produce a large strength improvement (43% increase from 434 MPa to 622 MPa) at no expense of ductility. On the contrary, Ni3Ti [14] Cu + NiAl -4%Ni [1] Cu + NiAl -2.5%Ni [1] NiAl -3%Mn [2] NiAl -no Mn [2] NiAl [3] Cu + NiAl [15] Cu + (Ti,Mo)C [16] (Ti,Mo)C [16] TiC [29] (Ti,Mo)C [29] k carbide [7] k carbide [27] NiAl [39] (b) Figure 3. A compilation of (a) yield strength increment and (b) ductility change against precipitate size of various precipitate strengthened steels.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations